Estimation of Ultraviolet Radiation Intensity under Cloudless Sky of Thailand - Sayan Phokate; Apiwat Boonkhuang (Science Technology and Engineering Journal (STEJ), 2022)
The purpose of this research is to estimate ultraviolet radiation intensity values using mathematical models. Ultraviolet intensity data obtained at a wavelength of 290-390 nm, along with global solar radiation and climate data on cloudless days. The case study of Thailand where the four solar radiation monitoring stations from the North, Northeast, Central and South among them are Chiang Mai, Ubon Ratchathani, Bangkok, and Songkhla provinces respectively. The models were created using data during 2017 to 2019. Following that, the model was validated using 2020 data on a cloudless days. It was found that the intensity of ultraviolet radiation was related to the ratio of solar radiation intensity at the Earth’s surface to extraterrestrial solar radiation intensity and the cosine of the zenith angle. In addition, the intensity of ultraviolet radiation is related to water vapor, ozone content, and visibility data. All of which can show mathematical relationships. The validation results of the model revealed reasonable agreement between the models with a positive correlation with one another. According to the results, all data are not significantly different at the 0.05 level.